Modelling Mt. Pinatubo climate effects - Graf, H.; Kirchner, I.; Schult, I. (1996)
The climatic impact of the Mt. Pinatubo volcanic eruption of June 1991 was studied by observations and model simulation for the first winter and summer after the eruption. A low resolution (T21) atmospheric GCM was driven by additional stratospheric aerosol derived from observations. The main results as observed and simulated are: Warming of the aerosol containing stratospheric layers resulting in an enhanced polar night jet. Reduction of the incoming shortwave radiation by 2 to 4 W/m-2. Modification of the tropospheric planetary wave structure in winter. During winter the induced advection leads to positive temperature anomalies in the lower troposphere over the midlatitude continents, while in summer the local radiation balance determines the volcanic impact and leads to slight cooling.